Throne-apse and 'Camara Santa'. The so-called Saint-Martin's Chapel in the Imperial Palace of Nijmegen (Bulletin KNOB, 1997)
As is shown by the names that are used for the ruined apse at the ‘Valkhof’ in Nijmegen, it is commonly believed that it belonged to the choir of the Palace-chapel and that it was built by the Emperor Frederick I Barbarossa. Until now no scholar has ever expressed any doubts about the function of the 'Barbarossa ruins' and in which period and by which of the rulers of the Holy Roman Empire it was erected.Nevertheless no thoroughly architectural research has been done that can be used as a solid basis for a reliable interpretation of the material, formal and functional aspects of the ruin. In this article, which is based on a more profound analysis of the material substance and the history of the architectural and sculptural forms that were applied by the masons, some very new conclusions are presented.The most important among them are undoubtedly that part of the building must be dated about 1045 and that it was never meant to be a Palatine double-chapel but, as far as the spaces are concerned on the first floor level, was built as the throne-apse of the Aula Regalis or royal assembly-hall.On the ground floor the holy relics of the saints and other precious liturgical objects, essential to the rituals that had to be observed during the royal visits to the palace, were kept and venerated in a sort of 'Camara Santa'. So it is supposed that in the apsidal room on the ground floor there was an altar that was dedicated to Saint-Martin, the original patron of the royal treasure of the Franks and consequently of every chapel in which it was temporarily deposited.